PETCO2 gradient: a novel prognostic parameter in cardiopulmonary exercise testing. (25th November 2020) - Poveda Pinedo, I.D; Marco Clement, I; Gonzalez, O; Ponz, I; Iniesta, A.M; Pena, L; Rodriguez, M.J; Hernandez, M.D; Arranz, H; Araujo, A; Marin, M; Espinosa, S; et al.
Abstract: Background: Previous parameters such as peak VO2, VE/VCO2 slope and OUES have been described to be prognostic in heart failure (HF). The aim of this study was to identify further prognostic factors of cardiopulmonary exercise testing (CPET) in HF patients. Methods: A retrospective analysis of HF patients who underwent CPET from January to November 2019 in a single centre was performed. PETCO2 gradient was defined by the difference between final PETCO2 and baseline PETCO2. HF events were defined as decompensated HF requiring hospital admission or IV diuretics, or decompensated HF resulting in death. Results: A total of 64 HF patients were assessed by CPET, HF events occurred in 8 (12.5%) patients. Baseline characteristics are shown in table 1. Patients having HF events had a negative PETCO2 gradient while patients not having events showed a positive PETCO2 gradient (−1.5 [IQR −4.8, 2.3] vs 3 [IQR 1, 5] mmHg; p=0.004). A multivariate Cox proportional-hazards regression analysis revealed that PETCO2 gradient was an independent predictor of HF events (HR 0.74, 95% CI [0.61–0.89]; p=0.002). Kaplan-Meier curves showed a significantly higher incidence of HF events in patients having negative gradients, p=0.002 (figure 1). Conclusion: PETCO2 gradient was demonstrated to be a prognostic parameter of CPET in HF patients in our study. Patients having negative gradients had worse outcomes by having more HF events. Funding Acknowledgement: Type of funding source: None